2022
DOI: 10.1002/ange.202203254
|View full text |Cite
|
Sign up to set email alerts
|

Four‐in‐One Stimulus‐Responsive Long‐Lived Luminescent Systems Based on Pyrene‐Doped Amorphous Polymers

Abstract: Materials exhibiting ultralong luminescent lifetime show promising applications in the fields of information encryption, sensing, and bioimaging. Herein, we present a low-cost and general strategy to achieve stimulus-responsive ultralong organic phosphorescence (UOP) based on pyrene chromophores doped into polymer matrices. The UOP of the resulted systems presents radiation-, concentration-, time-, and excitation-dependent characteristics. The UOP color can be turned from blue to red by changing the excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Information security plays a significant role not only in business and military fields but also in our daily lives. A number of information encryption technologies have been developed to reduce threats related to information security. , Among them, optical information encryptions have attracted attention due to the sensitive, intuitionistic, and convenient portability advantages. , In particular, multi-stimuli-responsive optical information encryption materials, which display visual color or fluorescence changes under various external stimuli such as light, heat, acid–base reagents, and mechanical forces, are more challenging to crack or imitate. There are research activities focusing on dual-modal responses triggered by single variate or triple-modal responses triggered by two variates. However, materials with quadruple-modal responses triggered by two variates for optimized performance without information redundancy have seldom been reported (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…Information security plays a significant role not only in business and military fields but also in our daily lives. A number of information encryption technologies have been developed to reduce threats related to information security. , Among them, optical information encryptions have attracted attention due to the sensitive, intuitionistic, and convenient portability advantages. , In particular, multi-stimuli-responsive optical information encryption materials, which display visual color or fluorescence changes under various external stimuli such as light, heat, acid–base reagents, and mechanical forces, are more challenging to crack or imitate. There are research activities focusing on dual-modal responses triggered by single variate or triple-modal responses triggered by two variates. However, materials with quadruple-modal responses triggered by two variates for optimized performance without information redundancy have seldom been reported (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, researchers have developed a novel and convenient method that utilizes polymers as flexible matrices and introduces different types of fluorescent small molecules. For example, Yuan et al employed sodium alginate as a matrix and introduced various aromatic compounds to obtain multicolor (from blue to red) p-RTP materials with excitation wavelength (λ ex )–dependent and time-dependent properties, and the reasonable explanation was provided by the cluster-triggered emission (CTE) mechanism. , Huang et al reported a feasible strategy that enables traditional poly­(4-vinylpyridine) derivatives to exhibit multicolor p-RTP emission . Yang et al successfully obtained a p-RTP system by doping fluorescent powder PBHDB into a poly­(methyl methacrylate) (PMMA) matrix. Based on the abovementioned strategies, in recent years, many researchers have used cellulose-based materials as the main body for chemical modification or physical doping and successfully prepared a series of long afterglow tunable cellulose-based materials. At present, research on this type of cellulose-based tunable long afterglow material mainly focuses on chemical modification. The cellulose-based dual and multicomponent systems that achieve wide color gamut and long afterglow tunable emission are achieved through chemical modification, and doping systems have hardly been reported.…”
Section: Introductionmentioning
confidence: 99%